The Effect Of Compensation, Work Motivation, Training On Employee Performance Through Job Satisfaction As An Intervening Variable - Fauzi Kurniawan; Hanif Mauludin; Yuyuk Liana (Lead Journal of Economy and Administration, 2024)
The study aims to examine the effect of compensation, work motivation, training on employee performance through job satisfaction as an intervening variable. The sample of this research is 81 employees at PT Cheil Jedang Indonesia Pasuruan. The main data source in this research is questionnaires. The data processing application uses Smart PLS. The results showed that compensation (X1) has a significant positive effect on job satisfaction (Z) of PT Cheil Jedang Indonesia Pasuruan employees. Work motivation (X1) has a significant positive influence on job satisfaction (Z) of PT Cheil Jedang Indonesia Pasuruan employees. Job Training (X1) has a significant positive influence on job satisfaction (Z) of PT Cheil Jedang Indonesia Pasuruan employees. Compensation (X1) has a significant positive influence on the performance (Y) of employees of PT Cheil Jedang Indonesia Pasuruan. Work Motivation (X1) has no influence on the performance (Y) of employees of PT Cheil Jedang Indonesia Pasuruan. Training (X1) has a significant positive influence on the performance (Y) of employees of PT Cheil Jedang Indonesia Pasuruan Job Satisfaction (X1) has a significant positive influence on the performance (Y) of employees of PT Cheil Jedang Indonesia Pasuruan. Job satisfaction (X1) can mediate the effect of compensation, work motivation and training on performance (Y).